Assessment with children who experience difficulty in mathematics. Issue 3 (August 2014) - Gillum, James
<x xml:space="preserve">Abstract</x> In recent years, there has been growing awareness of the impact that difficulties in mathematics can have on the life chances of children and young people. Consequently, a range of targeted interventions has been developed to support learners. However, when difficulties persist in spite of such intervention, next steps are not always clear. This article describes how assessment can be used in such cases, to build a better understanding of a child's situation and plan appropriate intervention. Two complimentary approaches to assessment are outlined: curriculum‐based assessment, which considers which parts of the maths curriculum a learner finds difficult and diagnostic assessment which asks why this might be so. Assessment tools and links between assessment and intervention are also discussed.